Acid-activated mixtures, cement slurries and structures
By urging the combination of magnesium-iron solid solution silicate filler with carbon dioxide, it promotes rapid curing of cement at low temperature and resists carbonization, solving the problem of slow curing speed and susceptibility to carbonization under low temperature conditions, and improving the strength of cement and durability.
Patent Information
- Application Number
- CN202380037513.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-09
- Filing Date
- 2023-04-04
- Publication Date
- 2025-01-17
AI Technical Summary
The existing cement has slow curing speed under low temperature conditions, delayed compressive strength development, and is easily affected by carbonation, resulting in a degradation in the application performance of concrete in cold environments.
Acid-excited magnesium-iron solid solution silicate filler is used to combine with carbon dioxide and gelling materials, absorb CO2 through the carbonation process, promote rapid curing of cement reaction at low temperatures, and form a protective layer to resist carbonization.
At low temperature, the strength and curing speed of cement are increased, the generation of CO2 is reduced, the durability of the cement structure is extended, and the resistance to carbonation is enhanced.
Smart Images

Figure BDA0005109981110000151 
Figure BDA0005109981110000161 
Figure BDA0005109981110000162
Abstract
Description
Technical Field
[0001] The present invention relates to an acid activated mixture, a method for producing an acid activated cement slurry, an acid activated cement slurry obtained by the method, uses of the acid activated cement slurry, a process for manufacturing an acid activated structure and an acid activated structure obtained by the process. More specifically, the present invention relates to an acid activated mixture, slurry and structure comprising an acid activated magnesium-iron solid solution silicate filler, a cementitious material, carbon dioxide and optionally an acid. Background Art
[0002] Since the 1960s, the use of cement and concrete additives has grown rapidly. The motivation is the desire to achieve all the good properties of concrete while avoiding the bad properties. With the advent of today's modern casting techniques and complex constructions, they have become completely dependent on additives. One such additive is air-entraining material (air-entrained concrete admixture). This is a liquid air-entrained concrete mixture formulated with modified naturally occurring and synthetic surfactants.
[0003] This complies with the requirements of EN 934-2 and promotes the distribution of microscopic air bubbles through the cement matrix.
[0004] ■Applications requiring high resistance to freeze-thaw cycles
[0005] ■Concrete that will be exposed to tidal conditions, splash zones and de-icing salts
[0006] ■ This provides the features and advantages of providing consistent bubble size and spacing
[0007] ■ Improved cohesion
[0008] ■ Improved machinability
[0009] ■Improved rheology
[0010] ■ Reduced permeability, reduced water bleeding
[0011] ■ Reduce the incubation period and improve the frost resistance of concrete
[0012] ■ Reduce air loss in fresh concrete
[0013] The density of concrete includes its density for liquids, gases, and ions, which is important for the function and durability of the structure.
[0014] Durability depends largely on the fact that corrosive liquids and gases do not penetrate into the concrete. In addition to the transport of liquids and gases, there is also the transport of ions in the stationary liquid (water) in the pore system. This is called diffusion.
[0015] The density of concrete and the liquid transport caused by the pressure gradient are mainly controlled by the mass ratio (W / C ratio) and the curing time. A low mass ratio leads to a small pore volume and a small proportion of coarse pores, so the concrete is relatively dense.
[0016] Any cracks and the degree of compaction in the concrete construction will also have some influence on the density of the concrete. The density of the cement binder depends on the size distribution of the pores and how well they are bonded together. The fine gel pores are connected, but due to the small size, most of the water is physically bound to the surface and will act as a transport route to a small extent.
[0017] The transport mechanism / diffusion of dissolved ions in the pore water is due to the inward concentration gradient in the pore water of the concrete for the ion type in question.
[0018] There are several different types of damage that can occur in concrete structures depending on the environmental stresses. Damage caused by long-term degradation mechanisms, damage caused by corrosion of the steel reinforcement due to pore water, has a reduced pH and does not seal the oxide layer on the steel. Carbonation of reinforced concrete causes the pH to drop from about 13 to about 9. This stops the corrosion protection of the concrete and the reinforcement begins to rust. This causes cracking of the reinforcement cover and subsequent spalling.
[0019] The risk of damage from carbonation can be reduced by increasing the thickness of the reinforced concrete cover, but this will increase costs significantly.
[0020] The solidification process of cement slurry is very complex. Many parameters will affect the final result. Among them, the curing temperature is one of the most important parameters.
[0021] In cold conditions, cement hydration slows dramatically or stops completely. Guidelines recommend that concrete curing temperatures must be maintained at >5°C (40°F) for at least 48 hours. Below this temperature, the chemical reactions required for concrete to set and strengthen are significantly slowed. The rate of initial setting and compressive strength development is significantly delayed as temperature decreases and W / C ratio increases. Most lead cement systems in use have high W / C ratios.
[0022] In order to function properly, cement must meet certain physical strength requirements. In order to meet these requirements, special care must be taken when curing at lower temperatures. In addition, it is important that the curing of the cement occurs quickly and without loss of strength.
[0023] At the wellhead of the Arctic seabed, the curing conditions of the lead cement close to the seabed are lower due to the lower seabed seawater temperature. Depending on the slurry temperature and its W / C ratio, it may take more than 36 hours to achieve the appropriate compressive strength.
[0024] Low temperature medium cure cement is not only important for applications in the oil and gas industry, but is also a factor in land-based cementing. Temperatures in many countries are below ideal cementing temperatures. This may include foundations, superstructures, parking structures, floor construction, tunnel construction and exterior surfaces, for example.
[0025] Curing has a significant impact on the properties of hardened concrete. Proper curing will improve durability, strength, impermeability, abrasion resistance, volume stability and frost resistance. These properties are negatively affected at low temperatures.
[0026] WO 2021 / 179067 relates to the use of an amorphous silica agent as a pozzolanic additive in concrete preparation and discloses a concrete mixture comprising a hydraulic binder, sand, aggregate, a cementitious material, an amorphous silica agent comprising SiO2 and active MgO.
[0027] US 4,422,496 discloses a process for preparing olivine sand cores and molds.
[0028] It is desirable to provide improved cement structures and processes for producing such improved structures. In addition, it is desirable to provide improved mixtures including cementitious materials and cement slurries that can be used to produce such cement slurries. Summary of the invention
[0029] The present invention solves many of the problems discussed above in the prior art. Acid activation will promote the curing of cement at all temperatures (including low temperatures). This gives concrete better structural properties.
[0030] Furthermore, the present invention can be used to sequester carbon dioxide and improve the castability of cement slurries. The present invention can form a protective layer to protect cement structures from carbonation without significantly increasing the thickness of the cement structures.
[0031] Magnesium-iron solid solution silicate can absorb CO2 through the carbonation process, as described herein. This is particularly useful for reducing CO2 during the curing process itself. In addition, it can absorb CO2 from the environment surrounding the curing process.
[0032] The more magnesium-iron solid solution silicate there is in the cement blend, the less total CO2 is produced and the more CO2 is absorbed. In addition, the additional amount of magnesium-iron solid solution silicate present also increases the amount of CO2 absorbed. This absorption is at least partially due to the carbonation reaction.
[0033] Therefore, one of the objects of the present invention is to use magnesium-iron solid solution silicates as fillers, which can stimulate cement pastes so that cement reactions occur at low temperatures. This makes cement stronger at low temperatures. In addition, this allows cements with higher W / C ratios to still maintain high enough strength to complete the relevant tasks. It can also cause cement reactions to occur at a higher rate.
[0034] Another object of the present invention is to provide a method for increasing cementing reaction speed at normal cementing temperature.
[0035] Yet another object of the present invention is to provide a cement structure that exhibits improved resistance to carbonation. Such improvements may result in less carbonation depth when the cement structure is exposed to CO2.
[0036] It is a further object of the present invention to provide improved mixtures, cement slurries and structures and methods of producing the same.
[0037] Thus, in one aspect, the present invention relates to an acid-activated mixture comprising:
[0038] - Acid activated magnesium-iron solid solution silicate filler;
[0039] - cementitious materials; and
[0040] - Carbon dioxide (CO2);
[0041] wherein the magnesium-iron solid solution silicate filler has a maximum of 7% free water, and wherein the magnesium-iron solid solution silicate filler is between 4% and 55% by weight of the cementitious material.
[0042] In another aspect, the present invention relates to a method for producing an acid activated cement slurry comprising the steps of:
[0043] a) preparing a slurry comprising a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material;
[0044] b) adding carbon dioxide (CO2) to the slurry; and
[0045] c) optionally adding an acid to the slurry;
[0046] The magnesium-iron solid solution silicate filler accounts for 4% to 55% of the cementitious material by weight.
[0047] In yet another aspect, the present invention relates to a process for making an acid-activated structure comprising the steps of:
[0048] i) preparing a slurry comprising a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material;
[0049] ii) introducing the slurry into a template;
[0050] iii) curing the slurry;
[0051] iv) adding carbon dioxide (CO2) to the slurry; and
[0052] v) optionally adding an acid to the slurry;
[0053] The magnesium-iron solid solution silicate filler accounts for 4% to 55% of the cementitious material by weight.
[0054] In a further aspect, the present invention relates to an acid-activated cement slurry obtainable by the process defined herein.
[0055] In a further aspect, the present invention relates to the use of the acid activated cement slurry as defined herein for the manufacture of an acid activated structure.
[0056] In a further aspect, the invention relates to an acid activated structure obtainable by a process as defined herein.
[0057] These and other objects and aspects of the present invention will be described in further detail below.
[0058] Definition and process
[0059] Hydration of cement
[0060] Water, when mixed with cement, forms a paste that binds aggregates together. Water hardens concrete through a process called hydration. Hydration is a chemical reaction in which the main compounds in cement form chemical bonds with water molecules and become hydrated or "produce" hydration products.
[0061] While there are several chemical reactions involved in mixing cement and water, there are two main exothermic reactions that determine the strength of the cured product:
[0062] 2Ca3SiO5+7H2O→3CaO . 2SiO2 . 4H2O+3Ca(OH)2+173.6kJ(calories)
[0063] 2Ca2SiO4+5H2O→3CaO . 2SiO2 . 4H2O+Ca(OH)2+58.6kJ(calories)
[0064] These reactions are temperature sensitive and slow (or stop) at low temperatures. Temperatures below 10°C (50°F) are detrimental to early strength development; below 4°C (40°F), early strength development is greatly slowed; and at temperatures at or below freezing, down to -10°C (14°F), little or no strength develops. For this reason, cement pastes are poured at temperatures above 15°C.
[0065] Hydration of magnesium-iron solid solution silicates
[0066] The hydration reactions described herein occur at the very low end of the pressure and temperature ranges typically discussed in metamorphic petrology. Diagenesis, weathering, and very low-grade metamorphism are the main processes. In geochemical reactions, an additional forcing of the reaction may be geochemical instability, in which unbalanced minerals or solutions attempt to react toward a stable state. In the present invention, artificially induced geochemical instability can be used to induce low-grade, very low-grade metamorphism, diagenesis, and weathering. Over time, even olivine particles immersed in an aqueous solution and placed at room temperature will weather into altered minerals.
[0067] Shown below are some reactions of the end-member olivines (forsterite and fayalite) when hydrated with H2O. It may occur according to, but is not limited to, the following reaction equations:
[0068] 3Mg2SiO4+SiO2+H2O→2Mg3Si2O5(OH)4
[0069]
[0070] as well as
[0071] 2Mg2SiO4+3H2O→Mg3Si2O5(OH)+Mg(OH)2
[0072]
[0073] as well as
[0074] 3Fe2SiO4+2H2O→2Fe3O4+3SiO2+2H2
[0075]
[0076] Note that forsterite is the magnesium end member of the olivine solid solution series, while fayalite is the ferrous end member of the olivine solid solution series. An olivine with 90% forsterite would be designated as FO90. The solid solution mineral series allows cations of similar size and valence to exchange at the same position in the lattice, based on the forces they are subject to. For olivine in natural systems, the magnesium end member indicates a higher crystallization temperature than the iron end member. Therefore, mantle rocks are mainly found in FO93-FO89 olivine. Pure forsterite is rare in nature.
[0077] According to the present invention, the similar reaction mode of magnesium-iron silicates in hydration reactions (with water (H2O) and related aqueous solutions (such as brines)) can be used so that the composition can be used as a reinforcing agent in cementitious mineral admixture materials, as a pozzolan, a latent hydraulic binder, as a filler for producing amorphous silica in a latent reaction, and generally to provide a natural antifouling agent in cementitious concrete and / or mortar structures.
[0078] Magnesium-iron solid solution silicate
[0079] The term "divalent magnesium-iron solid solution silicate" as used herein is a term from the field of geology and mineralogy. A common abbreviation in the art is "magnesium-iron silicate". In natural earth-based systems, there are more magnesium ions than iron ions.
[0080] Since it mainly involves Mg 2+ and Fe 2+ The "solid solution" chemistry of ions, magnesium-iron silicates, have variable compositions. These are silicate systems in which iron and magnesium ions can occupy the same position in the mineral. This is called substitution and can occur over a range of possible compositions because iron and magnesium have similar atomic radii ( and ), and may have the same valence.
[0081] For example, the formula of olivine is usually given as: (Mg,Fe)2SiO4. To those skilled in the art, olivine can be considered a mixture of Mg2SiO4 (forsterite - Fo) and Fe2SiO4 (fayalite - Fa). If there is more forsterite than fayalite (and therefore more magnesium than iron), then it can be called a magnesium-iron silicate. If there is more fayalite than forsterite, then it can be called an iron-magnesium silicate.
[0082] As another example, the formula of orthopyroxene is usually given as: (Mg,Fe)2Si2O6. To those skilled in the art, olivine can be considered a mixture of Mg2Si2O6 (enstatite-En) and Fe2Si2O6 (ferroxene). Orthopyroxene found in nature always has some Mg and pure feroxene can only be made artificially. Orthopyroxene with more Mg than Fe is called a magnesium-iron silicate. If there is more feroxene than enstatite, it can be called an iron-magnesium silicate.
[0083] filler
[0084] The term "filler" as used herein refers to materials whose function in concrete is primarily based on size and shape. They can interact with cement in several ways; thereby improving particle packing and imparting other properties to fresh concrete, and even reducing the amount of cement in concrete without losing strength. Ideally, fillers partially replace cement and simultaneously improve the properties and microstructure of concrete. Examples of suitable fillers include quartz, limestone, and other non-alkali reactive aggregates. Replacing cement with fillers generally results in a more economical product and improves the properties of cured concrete.
[0085] It is known that filler type and content can have a significant effect on fresh concrete properties, with non-pozzolanic fillers improving segregation and resistance to bleeding. In general, filler type and content can have a significant effect on unit weight, water absorption and void content. In addition, non-pozzolanic fillers may have a non-significant negative effect on concrete compressive strength.
[0086] Fillers as defined in NS-EN 12620 are aggregates with particles smaller than 2 mm. Fillers have a particle size where most of the particles pass through a 0.063 mm sieve. Fillers can be added to concrete in building materials to obtain certain properties. Fillers are the finest particle fraction of aggregates used in concrete and mortar. The fraction with a particle size smaller than 0.125 mm is called filler sand.
[0087] If the filler content is too high, the water demand may increase, resulting in reduced hardness and increased shrinkage.
[0088] Carbonation
[0089] The prior art discloses many examples of cement mineral mixtures used to produce concrete to prevent the cement structure from reacting with CO2, a process called carbonation. Carbonation is a well-known reaction that occurs in all lime cement mixtures, which changes its mineral composition from CaO (lime) to CaCO3 (calcium carbonate), and this change occurs naturally over time due to weathering. Magnesium-iron silicates also react with CO2, and the minerals formed due to carbonation expand into the gaps and cracks of the cementitious structure to keep the structure sealed.
[0090] Magnesium-iron silicates can be carbonated (e.g., altered by CO2) and thus increase the cement plug life of cement blends in wells, especially those penetrating carbon dioxide storage (CCS) reservoirs, when exposed to CO2. The reaction of olivine with CO2 may produce magnesium carbonate, forming a self-healing cement under realistic conditions in wells.
[0091] The following is an example of the carbonation process of magnesium end-member olivine reacting with carbon dioxide.
[0092] Mg2SiO4+2CO2→2MgCO3+SiO2
[0093]
[0094] Mg2Si2O6+2CO2→2MgCO3+2SiO2
[0095]
[0096] An example of a carbonation process occurs naturally, where CO2 reacts with the forsterite end member of the olivine solid solution series.
[0097] Dry Mix
[0098] In chemistry, the term "dry" can be difficult to unambiguously convey. One end of the scale is anhydrous (no water), while the other end is a slurry (enough water to make the mixture a liquid). Another issue when dealing with magnesium-iron solid solution silicates is the fact that water can be trapped in the crystal matrix. Water surrounding the outside of the crystal structure is called free water. Unless otherwise specified, "dry" means a free water content of 7% or less, preferably a free water content of 7% or less by weight.
[0099] acid
[0100] As used herein, the term "acid" refers to both strong acids and weak acids. As used herein, the term "strong acid" refers to an acid that completely dissociates into ions in water, producing one or more protons (hydrogen cations) per molecule. Examples of suitable strong acids include HCl (hydrochloric acid), HNO3 (nitric acid), H2SO4 (sulfuric acid), HBr (hydrobromic acid), HI (hydroiodic acid), HClO4 (perchloric acid), and HClO3 (chloric acid).
[0101] The term "weak acid" as used herein refers to an acid that does not completely dissociate into ions in water. For example, HF dissociates into H + and F -ions, but some HF remains in solution, so it is not a strong acid. Examples of suitable weak acids include HO2C2O2H (oxalic acid), H2SO3 (sulfurous acid), HSO4- (hydrogen sulfate ion), H3PO4 (phosphoric acid), HNO2 (nitrous acid), HF (hydrofluoric acid), HCO2H (formic acid), C6H5COOH (benzoic acid), CH3COOH (acetic acid), HCOOH (formic acid), and H2CO3 (carbonic acid).
[0102] Acid stimuli or stimulation
[0103] A magnesium-iron solid solution silicate filler that has been contacted with an acid (e.g., any of the acids mentioned herein) is referred to herein as an "acid-activated magnesium-iron solid solution silicate filler." If the filler has not been contacted with an acid, it will be referred to as a "non-activated magnesium-iron solid solution silicate filler." An acid-activated magnesium-iron solid solution silicate filler may also be referred to as an "acid-activated filler" or "activated filler." A non-acid-activated magnesium-iron solid solution silicate filler may be referred to as a "non-activated filler" or "non-acid-activated filler."
[0104] As used herein, the term "activator" is used as a shorthand for the property of the activating filler to accelerate the cement reaction, i.e., the concrete sets faster and / or allows the reaction to occur completely. An example is low temperature casting, which may not be possible without an activator to start the reaction.
[0105] Cement slurries using acid-activated magnesium-iron solid solution silicate fillers may be referred to herein as "activated cement slurries". Mixtures or dry mixtures including acid-activated magnesium-iron solid solution silicates may be referred to as "acid-activated mixtures" or "activated mixtures". Slurries including acid-activated magnesium-iron solid solution silicates may be referred to as acid-activated cement slurries or activated cement slurries. Structures made from acid-activated magnesium-iron solid solution silicates may be referred to as "acid-activated structures" or "activated structures".
[0106] Cementitious materials
[0107] As used herein, the term "cementitious material" refers to any cementitious material, such as, for example, any cement, Portland cement, and alkaline cement.
[0108] Structure and Templates
[0109] The term "structure" as used herein refers to the concrete casting. This is where the cement paste is added to the formwork and allowed to cure. The curing time and when the formwork is removed depends on the application. The formwork is usually removed before or after the concrete is able to withstand a full load (the industry standard is 28 days). In some applications, the concrete is fully cured before the formwork is removed.
[0110] The term "formwork" as used herein refers to a solid barrier that holds concrete in place or forces it to assume a particular shape during the curing process. Examples of suitable forms or concrete forms include wooden forms, cardboard tubes, and insulated concrete forms. In the case of mortar, the bricks in contact with the mortar act as formwork. In the case of applying cement slurry to a vertical surface (such as a tunnel wall), the formwork is the surface to which it is applied. In this context, vertical does not mean only for 90 degree angles to horizontal surfaces. DETAILED DESCRIPTION
[0111] Reference will now be made in detail to the present invention and embodiments thereof. Alternative embodiments will also be presented. However, the present invention can be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. These embodiments are provided by way of illustration only. Several additional embodiments or combinations of the embodiments presented will be within the scope of those skilled in the art.
[0112] The acid activated mixture according to the present invention comprises an acid activated magnesium-iron solid solution silicate filler; a cementitious material; and carbon dioxide; wherein the magnesium-iron solid solution silicate filler has a maximum of 7% free water, preferably a maximum of 7% free water by weight.
[0113] The method for producing an acid-activated cement slurry according to the present invention comprises the following steps: making a slurry comprising a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material; adding CO2 to the slurry; and optionally adding an acid to the slurry.
[0114] The process of manufacturing an acid-activated structure according to the present invention comprises the following steps: manufacturing a slurry comprising a non-acid activated magnesium-iron solid solution silicate filler, water and a cementitious material; introducing the slurry into a template; allowing the slurry to cure; adding CO2 to the slurry; and optionally adding an acid to the slurry.
[0115] In the mixture, method and process according to the present invention, the magnesium-iron solid solution silicate filler is preferably earth-based, or in the form of earth-based rocks or minerals. In addition, the magnesium-iron solid solution silicate filler can be selected from olivine, orthopyroxene, amphibole and serpentine, preferably olivine. Suitably, the magnesium-iron solid solution silicate filler is between 4% and 55% by weight of the cementitious material, preferably between 15% and 30% by weight of the cementitious material. The cementitious material can be selected from Portland cement and alkaline cement, preferably alkaline cement.
[0116] Examples of acids according to the mixture, method and process of the present invention include the above acids, and preferred examples of acids include H2CO3, HCOOH, CH3COOH, HCl, HNO3, H2SO4 and mixtures thereof. In a preferred embodiment, the acid preferably has a pH between 1 and 3.
[0117] According to the mixture, method and process of the present invention, carbon dioxide (CO2) is added to the mixture or slurry to preferably generate acid in situ. CO2 can be added to the mixture or slurry by adding CO2 in gaseous, solid or liquid form, suitably by adding CO2 gas, and preferably by bubbling CO2 gas through the mixture or slurry. According to the process of the present invention, CO2 can be added to the slurry in step i), step ii) or step iii), or between step i) and step ii), or between step ii) and step iii).
[0118] According to the method and process of the present invention, carbon dioxide (CO2) is added to a non-activated cement slurry, which is composed of at least cement, water and a non-activated magnesium-iron solid solution silicate filler. One method of achieving this is to bubble CO2 gas through the slurry. In this way, the CO2 gas will be absorbed before the structure is made. Without being bound by any theory, it is believed that the combination of water and CO2 results in the production of H2CO3 (carbonic acid). Although the carbonic acid will be neutralized in the cement slurry (as discussed above), it will not be in the area of direct contact with the non-acid activated magnesium-iron solid solution silicate filler. This contact will produce acid-activated magnesium-iron solid solution silicate filler in situ, thereby producing an activated cement slurry.
[0119] The bubbles of CO2 also have an effect on the slurry itself. The bubbles in the slurry make it easier to pour into the formwork. These bubbles can be removed by normal vibration and other methods well known in the art. However, according to a preferred embodiment of the present invention, the structure includes bubbles of CO2. Therefore, the structure or concrete can better withstand the expansion / freezing cycles in cold climates.
[0120] According to the mixture, method and process of the present invention, acid can be added to the mixture or slurry, and in a preferred embodiment, acid is added to the mixture or slurry. According to the method and process of the present invention, when the mixture or slurry includes a non-acid excited magnesium-iron solid solution silicate filler, acid is preferably added to the slurry. According to the process of the present invention, acid can be added to the slurry in step i), step ii) or step iii), or between step i) and step ii), or between step ii) and step iii).
[0121] The process of the present invention comprises a step of curing the slurry. The curing temperature may be between 0°C and 15°C, or between 0°C and 5°C, or between 5°C and 15°C.
[0122] The acid activated cement slurry according to the invention can be obtained by the method defined herein. The acid activated cement slurry according to the invention is suitable for making an acid activated structure, and the invention also relates to the use of the acid activated cement slurry according to the invention in making an acid activated structure. The acid activated structure according to the invention can be obtained by the process defined herein.
[0123] According to the present invention, it has been found that magnesium-iron solid solution silicate fillers can "initiate" cement reaction when mixed with acid. Preferably, such magnesium-iron solid solution silicates are in the form of earth-based rocks or minerals.
[0124] According to the present invention, the acid activated mixture is a combination of an acid activated magnesium-iron solid solution silicate filler and a cementitious material. One method of making an acid activated filler is to combine a non-acid activated magnesium-iron solid solution silicate filler with an aqueous acid. Examples of suitable acids include the acids described herein. The acid is then allowed to react with the filler. A pH range of between pH 1 and pH 3 is preferred, for example a pH of about 2. Suitably, the weight of the acid activated filler is between 4% and 55% by weight of the cementitious material, preferably between 15% and 30%.
[0125] The length of contact time between the acid and the filler may depend on the concentration of the acid and the type of acid. The filler can then be separated from the aqueous acid solution. This can be accomplished in several ways. One example is to place the mixture in a filter that is sized to filter out the filler but allow the aqueous acid to pass through. Another example is to heat the mixture until the acid evaporates. These two examples can be combined or used alone. This process of making an acid-activated mixture can also be repeated on an already acid-activated magnesium-iron solid solution silicate filler if it is desired to increase the acid concentration on the filler.
[0126] The method and process of the present invention include making a slurry, which includes a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material. The slurry can be prepared by mixing the non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and cementitious material in any order. For example, the slurry can be prepared by:
[0127] (i) adding water to a mixture of a non-acid activated or acid activated magnesium-iron solid solution silicate filler and a cementitious material;
[0128] (ii) adding water to the mixture of the non-acid activated magnesium-iron solid solution silicate filler and the cementitious material;
[0129] (iii) adding water to the mixture of the acid activated magnesium-iron solid solution silicate filler and the cementitious material;
[0130] (iv) mixing a cementitious material, a non-acid activated magnesium-iron solid solution silicate filler and water;
[0131] (v) mixing a cementitious material, an acid-activated magnesium-iron solid solution silicate filler and water;
[0132] (vi) adding an acid activated magnesium-iron solid solution silicate filler to a mixture of cementitious material and water;
[0133] (vii) adding a non-acid activated magnesium-iron solid solution silicate filler to a mixture of cementitious material and water;
[0134] (viii) adding a cementitious material to the mixture of the acid activated magnesium-iron solid solution silicate filler and water; and
[0135] (ix) Adding a cementitious material to the mixture of the non-acid activated magnesium-iron solid solution silicate filler and water.
[0136] According to the methods and processes of the present invention, carbon dioxide (CO2) and / or an acid may be added to the slurry prepared as defined in (i) to (ix) above, and carbon dioxide (CO2) and / or an acid may be combined with a non-acid activated magnesium-iron solid solution silicate filler, an acid activated magnesium-iron solid solution silicate filler, a cementitious material, water, and any mixture thereof.
[0137] According to the process of the present invention, the acid can be added to the structure by different methods. When a non-acid excited magnesium-iron solid solution silicate filler is used, it is not necessary for all of the non-acid excited magnesium-iron solid solution silicate to contact the acid. The acid can be applied to the surface and then the filler in contact with it is excited. The excited portion can generate heat and accelerate the curing process of the entire structure compared to a filler without excitement.
[0138] According to the process of the present invention, the acid may be introduced to at least one surface of the formwork. This may be done by spraying, painting, pouring, using a gel or other suitable means to hold the acid in place on the formwork. Then, a non-activated cement slurry may be added to the formwork and allowed to cure.
[0139] According to the process of the present invention, a non-activated cement slurry can be added to the formwork. Before the curing process is completed, an acid is applied to at least one surface of the structure. One example is to remove the formwork and then apply the acid. Another example is to apply the acid to the surface not covered by the formwork.
[0140] According to the process of the present invention, a non-activated cement slurry may be added to the formwork. Before the curing process is complete, CO2 may be applied to at least one surface of the structure.
[0141] Although the preferred magnesium-iron solid solution silicate filler is olivine, other examples include orthopyroxene, hornblende and serpentine. Magnesium-iron solid solution silicate fillers can also function as activators at higher temperatures. In this case, the cement reaction will occur faster than without this filler.
[0142] Magnesium-iron solid solution silicates as stimulating fillers act as stimulants, causing the cement reaction to occur in a shorter time frame than normal. Experiments conducted between 0-5°C showed that the setting of cement was below the recommended setting temperature of cement. Cement was not expected to set before 28 days at this temperature. Note that the 5-15°C range is also considered cold, and the expected setting time is 24-48 hours. The addition of magnesium-iron solid solution silicates can reduce this setting time without significant strength loss.
[0143] A reduction in setting time, i.e. an increase in the rate of cement reaction, may also occur at temperatures above 15°C to the more typical temperatures at which cement sets.
[0144] Example
[0145] The present invention is further illustrated in the following examples, which are, however, not intended to limit the present invention. Unless otherwise indicated, parts, % and ratios relate to parts by weight, % by weight and weight ratio, respectively.
[0146] Example 1
[0147] Mixtures, cement slurries and structures according to the present invention and corresponding products for comparison were prepared, and the obtained structures were tested and evaluated for carbonation resistance.
[0148] Four different cementitious materials or cements were used. The filler used according to the invention was olivine, which was non-acid activated before the obtained slurry or mixture was placed in carbon dioxide (CO2). The filler used for comparison was quartz. The mixtures obtained and the amounts of the components used can be seen from Table 1. The slurry was prepared by mixing the cementitious materials with the fillers and then adding water to the obtained mixture.
[0149] For the tests, samples of size 40 / 40 / 160 mm were cast from each mix. After demoulding, the samples were stored in water for 13 days and then exposed to air containing 1% CO2 in a cabinet at 20°C and 60% RH. The carbonation depth was measured after 4, 8, 12 and 22 weeks of exposure in the cabinet.
[0150] The mixtures and results are shown in Table 1.
[0151] Table 1
[0152]
[0153]
[0154] As can be seen from Table 1, the samples (structures) prepared from the mixture (cement slurry) according to the present invention showed less carbonation depth after 4, 8, 12 and 22 weeks of exposure to 1% CO2 and thus were better resistant to carbonation than the comparative samples.
[0155] Example 2
[0156] The procedure according to Example 1 was repeated, except that the sample preparation was slightly different and an acid was used in common when preparing the sample. As in the example, the obtained samples were tested and evaluated for carbonation resistance.
[0157] The samples were stored in the template for one day, in water for 3 days, and in air at 65% RH for 3 days, and then subjected to acid treatment using 5% hydrochloric acid (HCl) and 5% nitric acid (HNO3). The acid treatment was performed by soaking one sample in each mixture in hydrochloric acid (HCl) and nitric acid (HNO3) for 12 minutes respectively. Each sample used as a reference was soaked in pure water.
[0158] After treatment with acid and water respectively, the samples were packed together in plastic foil. After 15 days, the samples were unpacked and placed in a cabinet containing 1% CO2 atmosphere at 20C and 60% RH. Disintegration and carbonation depth measurements were performed after 4, 9 and 22 weeks of exposure.
[0159] The mixtures and results are shown in Table 2.
[0160] Table 2
[0161]
[0162]
[0163] As can be seen from Table 2, the samples (structures) prepared from the acid activated (treated) mixture and cement slurry according to the present invention showed less carbonation depth after 4, 9 and 22 weeks of exposure to 1% CO2, and therefore were better able to resist carbonation than the comparative samples.
Claims
1. An acid-activated mixture comprising: - Acid activated magnesium-iron solid solution silicate filler; - cementitious materials; as well as - Carbon dioxide (CO2); wherein the magnesium-iron solid solution silicate filler has a maximum of 7% free water; and wherein the magnesium-iron solid solution silicate filler is between 4% and 55% by weight of the cementitious material.
2. A method for producing an acid activated cement slurry, comprising the steps of: a) preparing a slurry comprising a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material; b) adding carbon dioxide (CO2) to the slurry; and c) optionally adding an acid to the slurry; in, The magnesium-iron solid solution silicate filler is between 4% and 55% by weight of the cementitious material.
3. A process for making an acid-activated structure comprising the steps of: i) preparing a slurry comprising a non-acid activated or acid activated magnesium-iron solid solution silicate filler, water and a cementitious material; ii) introducing the slurry into a template; iii) allowing the slurry to solidify; iv) adding carbon dioxide (CO2) to the slurry; and v) optionally adding an acid to the slurry; The magnesium-iron solid solution silicate filler accounts for 4% to 55% of the cementitious material by weight.
4. The mixture according to claim 1, the method according to claim 2 or the process according to claim 3, wherein The magnesium-iron solid solution silicate filler is earth-based, or in the form of earth-based rocks or minerals.
5. The mixture according to claim 1 or 4, the method according to claim 2 or 4 or the process according to claim 3 or 4, wherein The magnesium-iron solid solution silicate filler is selected from olivine, orthopyroxene, hornblende and serpentine, preferably olivine.
6. The mixture according to any one of claims 1, 4 and 5, the method according to any one of claims 2, 4 and 5 or the process according to any one of claims 3 to 5, wherein The magnesium-iron solid solution silicate filler is between 15% and 30% by weight of the cementitious material.
7. The mixture according to any one of claims 1 and 4 to 6, the method according to any one of claims 2 and 4 to 6 or the process according to any one of claims 3 to 6, wherein The cementitious material is Portland cement or alkaline cement, preferably alkaline cement.
8. The mixture according to any one of claims 1 and 4 to 7, the method according to any one of claims 2 and 4 to 7 or the process according to any one of claims 3 to 7, wherein The acid has a pH between 1 and 3.
9. The mixture according to any one of claims 1 and 4 to 8, the method according to any one of claims 2 and 4 to 8 or the process according to any one of claims 3 to 8, wherein The acid is H2CO3, HCOOH, CH3COOH, HCl, HNO3 and / or H2SO4.
10. The method according to any one of claims 2 and 4 to 9 or the process according to any one of claims 3 to 9, wherein Adding carbon dioxide (CO2) to the slurry generates acid in situ.
11. A method according to any one of claims 2 and 4 to 10 or a process according to any one of claims 3 to 10, wherein Adding carbon dioxide (CO 2 ) to the slurry includes adding CO 2 gas, preferably bubbling CO 2 gas through the slurry.
12. A method according to any one of claims 2 and 4 to 11 or a process according to any one of claims 3 to 11, wherein Adding carbon dioxide (CO 2 ) to the slurry includes adding CO 2 in solid or liquid form.
13. A method according to any one of claims 2 and 4 to 12 or a process according to any one of claims 3 to 12, wherein This involves adding an acid to the slurry.
14. A method according to any one of claims 2 and 4 to 13 or a process according to any one of claims 3 to 13, wherein The slurry is made by adding water to a mixture of non-acid activated or acid activated magnesium-iron solid solution silicate filler and cementitious material.
15. A process according to any one of claims 3 to 14, wherein Carbon dioxide (CO2) is added to the slurry in step i), step ii) or step iii), or between step i) and step ii), or between step ii) and step iii).
16. A process according to any one of claims 3 to 15, wherein The acid is added to the slurry in step i), step ii) or step iii), or between step i) and step ii), or between step ii) and step iii).
17. A process according to any one of claims 3 to 16, wherein The curing temperature is between 0°C and 15°C, or between 0°C and 5°C, or between 5°C and 15°C.
18. An acid activated cement slurry obtainable by the method according to any one of claims 2 and 4 to 14.
19. Use of the acid activated cement slurry according to claim 18 for manufacturing an acid activated structure.
20. An acid-activated structure obtainable by a process according to any one of claims 3 to 17.
Citation Information
Patent Citations
Process for preparing olivine sand cores and molds
US4422496A
Use of amorphous silica reagent produced from serpentine in concrete preparation
WO2021179067A1